Index of anthropogenic load on land (ALOL) as decision support method in territorial planning - Gaudėšius, Rimvydas (Journal of Environmental Engineering and Landscape Management, 2020)
Not all international indexes of sustainability can be easily applied to Lithuanian specialists who organize territorial planning documents. Therefore, the index assessing the anthropogenic impact can be applied in spatial planning documents is required. The proposed method is beneficial in a way that it is based on the available free statistics data. Not only land use changes can be assessed by using presented ALOL index, but also newly presented spatial planning documents. The anthropogenic load on the land index have been calculated and the comparison with another popular multi-criteria decision support methods was conducted in this study. The results showed that the value of the anthropogenic load index is deteriorating in one of the Lithuanian metropolitan areas and the proposed method does not let others down with the precision for other mathematical methods.